D3.1. Assessment of the Action Plan and of regional instruments - Final version - (:unkn) unknown (My University, 2018)
According to the Global Status Report on Road Safety 2015 of WHO (WHO, 2015), 'road traffic injuries claim more than 1.2 million lives each year and have a huge impact on health and development'. Using WHO classification of regions, there has been a further deterioration in road fatality rates in the WHO Africa region from 24.1 fatalities per 100,000 populations in 2010 to 26.6 fatalities per 100,000 in 2013. Over the same period, there was a further improvement in road fatality rates in the WHO Europe region. Road trauma in Africa is expected to get worse, with fatalities per capita projected to double over the period 20152030 (Small and Runji, 2014). SaferAfrica project aims at establishing a Dialogue Platform between Africa and Europe focused on road safety and traffic management issues. It will represent a high-level body with the main objective of providing recommendations to update the African Road Safety Action Plan and the African Road Safety Charter, as well as fostering the adoption of specific initiatives, properly funded. The main objective of work package 3 is to assess the implementation of the Action Plan 2011-2020 (AUUNECA, 2010). This assessment has been supported by SWOT and PESTEL analysis completed at different geopolitical scales (continental, regional economic communities/corridors and country). The second main objective is to define some initiatives for different topics designed to foster the implementation of the Action Plan. The initiatives will be based on the outputs of WP3, WP4, WP5 and WP6 and will address technical, administrative and economic concerns. The aim is to prepare turnkey project for the Dialogue Platform Management Board. The objective of Task 3.1 on which is based this deliverable is the Assessment of the implementation of the Action Plan and of regional instruments. The analysis has been realized at different spatial levels, country, corridor and continental levels. For the continent
Keywords: African Research